Effectiveness of Coconut Water and Atonics on the Growth of Eggplant (Solanum melongena) Seedlings of the Laguna F1 Variety: EFEKTIVITAS PEMBERIAN AIR KELAPA DAN ATONIK TERHADAP PERTUMBUHAN KECAMBAH TERONG UNGU (Solanum melongena) VARIETAS LAGUNA F1 - Wulandari, Adelia saviera; Handayani, Tundjung Tripeni; Handayani, Kusuma; Wahyuningsih, Sri (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
Eggplant (Solanum melongena L.) is an authentic plant native to tropical climates, widely favored by the community, and available at an affordable price. The demand for eggplant in Indonesia reached 69,963 tons in 2015 and has continued to increase to 74,081 tons. Based on FAO data in 2016, Indonesia is one of the eggplant-producing countries, ranking sixth in the world after China, India, Egypt, and Turkey. The Laguna F1 eggplant variety is known for its quality and resistance to bacteria-causing wilting. To minimize the cultivation time of eggplants, it is necessary to use readily available natural fertilizers, one of which is coconut water. The utilization of coconut water as fertilizer is due to its content of various hormones that play a crucial role in plant growth, namely auxin, cytokinin, and gibberellin. The purpose of this research is to investigate the effects of coconut water and atonic, determine the optimum concentrations, and understand the interaction between coconut water and atonic in the growth of eggplant plants. The research was conducted in the Botany Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Lampung, in October-November 2019, using a 2x3 factorial design. The first factor involved coconut water at concentration levels of 25%, and 50%, and compared with a control group (0%). The second factor was the atonic solution with a concentration of 10 ml/l, compared with a control. The treatments were repeated in five replications, resulting in 30 experimental units. Observed variables included plant height, fresh weight, dry weight, relative water content, and chlorophyll content. The results of this research can be summarized as follows: the application of coconut water and atonic has a positive effect on the growth of eggplant plants. Additionally, the combined induction of coconut water at a concentration level of 25% and atonic at 0% demonstrated superior outcomes in terms of plant height, fresh weight, dry weight, relative water content, and chlorophyll content in eggplant plants.